PENGARUH PROMOSI PENJUALAN DAN ATMOSFER TOKO TERHADAP PEMBELIAN IMPULSIF PADA MATAHARI CILANDAK TOWN SQUARE - Muhammad Naufal Fadhillah, - (2019)
Retail business in Indonesia has a fairly good development. So the pattern of public spending has high expectations as well. As one of the modern retail business, Matahari must have the advantage to be able to compete and survive in the business. Matahari itself is one of the retail companies in Indonesia that offers a variety of products needs community. This study was conducted to examine the effect of sales promotion and store atmosphere on impulse buying. Data collection using questionnaires with Likert scale with PLS (Partial Least Square) method with SmartPLS3.0 software. The sample used in this research is 100 people. The technique of determining the sample using accidental sampling method. The results of this study indicate that sales promotion variables significantly influence impulse buying and store atmosphere variables have a significant effect on impulse buying.